Social reproduction: the sidelined aspect in gender and agricultural research - Kawarazuka, Nozomi; Hoa, Pham Thi; Huyen, Le Thi Thanh; Trang, Bui; Achandi, Esther Leah (Frontiers in Sustainable Food Systems, 2023)
This study explores women's agribusiness by employing feminist theories to gain an understanding of the gender dimension of business beyond economic value, including non-material and non-market aspects associated with social reproduction.We conducted fieldwork between July and October 2021 in Vietnam through in-depth interviews with 16 women entrepreneurs in towns on the border with China, who engage in livestock-trading, and in the Central Highlands, who engage in domestic and international horticultural trade. Our findings confirm that women entrepreneurs manage their business, family, and family relations together as one consolidated commitment in flexible, informal, and creative ways. Research focusing solely on economic analyses obscures not only women's hidden labor and time in the household that enable men to dominate agribusiness, but also women's resistance to male-privileged agribusiness.Positioning social reproduction at the center of women's economic activities enables researchers to have a full picture of how male-privileged agri-food systems are sustained, which is the first step towards disrupting existing inequalities in agri-food systems.provisioning, maintaining kinship), tending to frame gender narrowly within the aspect of economic activities. The fundamental challenges women face in agriculture lie in the realm of social reproduction and its relationship with economic activities, but these remain unexplored. This leads researchers to misconceive the problems of gender in agricultural entrepreneurship as well as agrifood systems. For example, substantial evidence from economics-focused agricultural research explains that women lack access to markets, financial capital, technologies, entrepreneurial skills and knowledge compared to male counterparts (Babu, Manvatkar, and Kolavalli 2016;Dvouletý and Orel 2020;Lourenço 2014;Murphy et al. 2020). These women-lack-of narratives attribute women's problems as technological and individual instead of political and structural. Recommendations drawing on such narratives are to provide more training and financial support to "close the gender gap" and "empower" individual women. In consequence, the underlying structural problems that persistently disadvantage women are unaddressed, leaving individual women in disadvantageous conditions (